Surge of Divorce in Lahore, its Exploring Factors and Possible Solutions, Pakistan - Khaleek, Shahid Qayyum; Hussain, Abid (Advances in Social Sciences Research Journal, 2015)
The study had been documented in Lahore city. The objectives of the study were to find factors of divorce and possible solutions to minimize the surge of divorce. The present study was qualitative in nature. For covering all the objectives comprehensively, there were forty two participants in total figure including both the genders and taken form three different segments of the population like divorced people selected using snow-ball sampling technique, lawyers were accessed using convenient sampling technique and married people were also approached who conveniently available at the time of data collection. An unstructured check list was prepared to collect the information with regard to study objectives. In view of findings, results demonstrate there was no single factor leads to divorce but many like economic instability, greed of dowry and wealth, unemployment, disparity in education, joint family system, exchange marriages, early age marriages, birth of girl child, dual marriages, disparity in social status , external pressures, forced and pressurized marriages, spousal illegal relationships, unrealistic expectations, fraud in marriages ,drug abusing, age incompatibility, mental incompatibility, infertility, short-temperament or patience , lack of compromises or sacrifices, egoistical issues. In lieu of effects, divorce left many heinous psychological, social, economic effects on both the gender victims which may further become the cause in personality disorder. With regard to solutions which may be impediments in breaking the legal agreement between male and female like compromise and sacrifices, patience and endurance, empathetic way of analysis, develop feeling of “We” not “I”, respect and honor, caring in every matter of life, no space for lie or mistrust, freedom of speech, egalitarian approach in decision making, sharing gifts and pleasures, caring about liking and disliking, pardon on mistakes, respect for family and relatives not by one part but from both the sides.